Regeneration Status of Some Important Moist Deciduous Forest Trees in the Trichur Forest Division - Narayanan Illath Valappil (College of Forestry, 1988)
Sustained management of forests depends on their ability to regenerate. The pace at which the older trees are replaced by younger ones, is very important in this respect. The details of sylvigenesis is little known, especially of the moist deciduous forests. To get a general idea of the regeneration behaviour of the moist deciduous forests eight localities of varying levels of disturbance were sampled in the Trichur Forest Division. Enumeration of trees and their regeneration were done and data were analysed at three levels of organization, viz. ecosystem level, stratum level and species level. Physiognomically the moist deciduous forests comprise three vertical strata namely, upper, middle and the lower. The middle stratum is richest in species. Most of the species represented in the upper stratum are commercially important. Five species, Dillenia pentagyna, Grewia tiliifolia, Lagerstroemia microcarpa, Terminalia paniculata and xylia xylocarpa, occupying the upper stratum, possess higher values of basal area, relative basal area, density per hectare, relative density and importance value index, and are the dominant ones. The average growing stock of desirable commercially important species > = 20 cm DBH per hectare is 149.79. This is slightly lower than the average of 167 trees/ha cited by Seth and Kaul. The growing stock of trees > = 1 cm DBH, of the middle and lower strata decrease exponentially with increasing cover gaps. The upper stratum on the other hand is not much affected by disturbance. In fact, with slight disturbance it increases a little. Relative importance value index of the middle stratum increases where that of the lower straum decreases and vice versa. Frequency distribution statistic for stands and strata conform to the negatively exponential model. Mortality rates are maximum in the lower size classes. Comparison of observed frequencies of unestablished seedlings to the expected frequencies of the commercially important stratum indicates that the reproductive potential of stands is not poor. On the other hand, the growing stock of established seedlings (saplings + poles) is very low. Owing to very low survival probability in the sapling stage acute paucity of poles of the upper stratum is observed. The five dominant species show the same pattern of population structure and distribution of survival probability as the stratum. Regeneration of important species in the moist deciduous forests is under various stresses of which that of human origin is the most hazardous. Grazing, browsing, fire, and illicit cutting are the greatest constraints. Some species like Lagerstroemia microcarpa also show some intrinsic constraints.